Otolith increment width-based chronologies disclose temperature and density-dependent effects on demersal fish growth. (17th December 2019) - Vieira, Ana Rita; Dores, Sandra; Azevedo, Manuela; Tanner, Susanne E
Abstract: Climate change and fishing are drastically impacting marine ecosystems. Comprehending the biological consequences of these effects on commercially exploited fish is especially challenging. Here, we developed a 43-year otolith increment width-based growth chronology for one of the most important commercially exploited fish species in the Northeast Atlantic (European hake, Merluccius merluccius ). Increasingly complex linear mixed-effects models were used to partition growth variation into intrinsic (age, sex, and age-at-capture) and extrinsic (environmental and biotic variables) factors, allowing age interaction with extrinsic variables to assess age-dependent responses in growth. Our results provided strong evidence that European hake growth is impacted by ocean temperature, namely sea surface temperature and temperature at depth, and species abundance (recruitment), with different responses depending on fish age. We found evidence that increasing ocean temperature could be highly detrimental for species growth especially during the first years of life. We provided insights into the effects of environmental and biotic factors on species growth variation. Such information is key to recognize the sensitivity of European hake growth to climate change, which may contribute to sustainable management policies for this valuable resource.